Evaluation of Nitrogen Fertilizer and Plant Density on Chemical Analysis of Corn Forage and Weed Population in an Agroforestry System - Ghanbarzade, S.; Chaichi, M.R.; Hosseini, S.M.B.; Sadeghpour, A. (Asian Journal of Chemistry, 2010)
Agroforestry is one of the aspects of sustainable agriculture in which woody perennials are deliberately integrated with crops and/or animals in the same place, in the same time or both. This study was conducted to analyze the effects of nitrogen fertilizer and corn density under the canopy of orange trees on forage chemical analysis and weed populations. In this experiment, 4 levels of nitrogen fertilizer (0, 100, 200 and 300 kg/ha) and 4 different levels of corn densities (80000, 110000, 140000 and 170000 plants/ha) were used in a split plot arrangement based on randomized complete blocks design with three replications in Babol (Babol kenar region), Iran. The increasing of nitrogen fertilizer caused a raise in crude protein percentage and the highest percentage of crude protein was obtained in the 300 kg/ha nitrogen fertilizer and population of 110000 plant/ha. The highest digestive dry matter was yielded in the 200 kg/ha of N fertilizer and 110000 plant/ha. Moreover, by increasing of nitrogen fertilizer and sowing rate, weeds dry matter decreased and the lowest amount of weeds biomass was observed in 300 kg/ha nitrogen fertilizer and sowing density of 170000 plant/ha.